Estimation of Insulin Resistance in Obese Adults in Baghdad - Taha, Bareq E.; Majeed, Maysaa J. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Insulin works to control blood sugar levels by sending signals to the liver, muscle, and fat cells to bring sugar out of the blood. Obesity, hyperinsulinemia, hyperglycemia, and hyperlipidemia are only a few of the interconnected metabolic disorders that are frequently linked to these diseases. Objective: To study the effects and help Triglyceride-Glucose Index and Homeometric Assessment Model–IR (TyG & HOMA-IR) of knowing insulin resistance and early detection of prediabetes. Method: The study was conducted on 160 volunteers, recruited from an age group based on the study data and the preliminary analysis, with ages ranging from 40 to 70 years. They were grouped into two groups: The first includes 80 individuals with a body mass index of more than 25/m2, who suffer from insulin resistance, and the second group includes 80 healthy individuals who do not suffer from insulin resistance and whose body mass index is less than 25 kg/m. 2Measurement of serum glycine using ELISA kits. Results: After conducting the statistical procedures for the results of the subjects for each of TyG and HOMA-IR, it was found that there was a significant change and p-value (0.00). Both markers of IR (TyG index and HOMA-IR) show that the TyG index and HOMA-IR had significant positive correlations with each of fasting serum glucose, insulin, and blood HbA1c%. Conclusion: HOMA-IR has had an important role in the evaluation, detection, and prognosis of prediabetes. It also helps detect early complications associated with T2DM and helps determine the best treatment options. It also found that the TyG index beats the HOMA-IR for predicting prediabetes. It has the best potential for early detection and prevention of prediabetes.